A proposed method for mathematical quantitative description of fractures from borehole wall images. Issue 4 (October 2020) - Han, Zengqiang; Wang, Chuanying; Jiao, Yuyong; Wang, Chao; Wang, Jinchao
Abstract: Fractures from borehole wall images are different from those from surface outcrop in trace pattern, distribution pattern, parameters description and so on. Focus on the geometric parameters of fractures from borehole images, a method for mathematical quantitative description of these fractures is proposed. The fracture from borehole images is described into a point in spatial coordinate system, and this point is defined Fracture Feature Point. The key parameters including dip direction, dip angle and position depth of fractures from borehole wall images are converted into coordinates of fractures feature points. The related calculation equations are deduced in local coordinate system and spatial coordinate system. Furtherly, the space distribution regularities of the fractures based on the distribution characteristics of fracture feature points are summarized. Typical application in multiple boreholes of this description method is studied and an analysis method for any two fractures' connectivity is established based on Fracture Feature Point. The results of an engineering example research show that the method is effective in fractures connectivity analysis. The mathematical quantitative description method of fractures from borehole wall images will provide new ideas of the research on deep rock mass structure.